Kitchen scale : a measure that reflects societal change - Þórdís Timila Guðmundsdóttir 2000- (2023)
Domestic architecture spaces are designed for specific roles. An example is the concept of the kitchen, a space for cooking and storage. The multi functional space of the kitchen has altered with the rise of feminism – and its role reflects societal change. The kitchen is essential element in the function of nurturing our bodies. The kitchen is not a static phenomenon. It varies between countries. It has also changed over time reflecting increased economic prosperity and the development of ideas about gender equality, new technologies etc. This paper is an examination of these differences – between cultures and climate areas as well as over time. We will look at the development of the role and design of kitchens over a period of time within Iceland.